IMMUNOLOGICAL REACTIVITY CHANGES IN PERIODONTITIS OF BACTERIAL-IMMUNOGENIC GENESIS UNDER THE CONDITIONS OF USE OF VARIOUS METAL CROWNS - Marfiian, Oleh V.; Demkovych, Andrii Ye. (Eastern Ukrainian Medical Journal, 2026)
Introduction. Metal non-removable orthopedic structures that are fixed in the oral cavity are subject to biological destruction, which affects the mechanisms of regulation of both specific and nonspecific tissue resistance. This can cause a decrease in local immunity. The aim of this work was to investigate the disruption of the humoral link of the immune system in experimental periodontitis of bacterial-immune genesis under the condition of using different types of metal crowns. Methods. In experimental animals, experimental periodontitis was modeled by injecting into the periodontal tissues a suspension containing a mixture of microorganisms (Staphylococcus aureus and Streptococcus hemolyticus) based on egg white. The study of disorders of the humoral immune system was carried out by determining the content of immunoglobulins of classes A, M and G and the amount of circulating immune complexes in the blood serum on the 30th day of the experiment both without and with stamped and cast crowns fixed in the oral cavity. Results. The results of the study showed that the development of periodontitis of bacterial-immune genesis is accompanied by the activation of the humoral link of immunity, which is manifested by an increase in the levels of immunoglobulins A, M, G and circulating immune complexes in the blood serum. The use of fixed prosthetics affected the immune response of the body: cast crowns caused a higher level of immunoglobulins compared to stamped crowns, however, prosthetics were generally associated with a decrease in humoral immunity compared to the group of animals that had only an inflammatory process without prosthetics. Conclusion. The increase in the level of immunoglobulins and circulating immune complexes on the 30th day in animals with periodontitis confirms the activation of the humoral link of immunity. The use of metal fixed prosthetic structures affects the immunological status of the body, and cast crowns caused more pronounced changes compared to stamped ones.